Morton neuroma: Comparative results of two conservative methods - KARADAĞ SAYGI, NAİME EVRİM (AMER ORTHOPAEDIC FOOT & ANKLE SOC, INC, 2005)
Background. The initial treatment of Morton neuromas consists of conservative methods that include shoe modifications and steroid injections. The purpose of this prospective study was to compare the efficacy of these two methods to determine which is more effective as the initial treatment method. Methods: Eighty-two patients with Morton neuromas were randomly assigned to receive either footwear modification with orthoses or steroid injections as initial treatment. Outcomes were evaluated at 1 month, 6 months, and 12 months. Results: Patient satisfaction was significantly better (p < 0.01) in the group treated with steroid injections than those treated with shoe modifications at all three followup intervals. At 12-month followup, 82% of those treated with steroid injections had complete or partial relief of pain compared to 63% of those treated with footwear modifications alone. Conclusion: Steroid injections as initial treatment and shoe modifications with steroid injections at 6 months appear to give better results in Morton neuromas than shoe modifications alone, but the difference in the two groups were not statistically significant at one year followup.
Keywords: conservative treatment; morton neuroma; steroid injection; INTERDIGITAL NEUROMA